2008
DOI: 10.1080/13668250701875137
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity among children with developmental disabilities

Abstract: The prevalence of overweight and obesity is higher among children with developmental disabilities than in the general population. Community-based studies with larger sample sizes are required to confirm this finding. The results also highlight the need to develop health care strategies for the prevention, early identification and management of excess weight gain for this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 18 publications
6
76
1
4
Order By: Relevance
“…However, it has been shown that extracurricular sports play an important role in acquiring healthy lifestyle habits. This study confirms what De, Small and Baur (2008) argue and shows that physical educators are committed to teaching their students to adopt an active lifestyle and try to create opportunities outside physical education classes to stimulate participation in recreational and competitive physical activity. Physical education teachers are involved on this level during school hours (classes and lunchtime activities), but also outside these periods (after classes and during extracurricular activities).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, it has been shown that extracurricular sports play an important role in acquiring healthy lifestyle habits. This study confirms what De, Small and Baur (2008) argue and shows that physical educators are committed to teaching their students to adopt an active lifestyle and try to create opportunities outside physical education classes to stimulate participation in recreational and competitive physical activity. Physical education teachers are involved on this level during school hours (classes and lunchtime activities), but also outside these periods (after classes and during extracurricular activities).…”
Section: Discussionsupporting
confidence: 74%
“…In addition, schools play an essential role in acquiring a healthy lifestyle. They can instill good PA habits, especially in young people with disabilities (De, Small & Baur, 2008). Some authors even add that schools should become providers of physical activity by facilitating and initiating participation in sports (Dugas & Point, 2014).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Furthermore, research indicates that specific disability groups are associated with the highest body mass indices (BMI): autism, spina bifida with co-occurring ID, and Down syndrome (Rimmer et al, 2010). Additionally, females with ID are more likely to have higher levels of overweight and obesity than their male counterparts (De, Small, & Baur, 2008). There are a number of factors that contribute to the increased prevalence of obesity in individuals with significant disabilities.…”
Section: Obesity: Prevalence and Contributing Factorsmentioning
confidence: 99%
“…Several studies have shown that childhood obesity has a negative impact on children ages 3-15 yr (Brisbois et al, 2012;De et al, 2008;Kantomaa et al, 2013;Lane & Bundy, 2011). The findings of this research study confirm these earlier findings and have further important implications for occupational therapy practice:…”
Section: Implications For Occupational Therapy Practicementioning
confidence: 99%